Une linguistique au-delà de l’humain ? - Chloé Mondémé (Itinéraires)
This article aims to discuss the relevance of considering an interspecies semiosis, both in theoretical and empirical terms. It revisits the recent work of anthropologist Eduardo Kohn, who claims for an “anthropology beyond the human” (2013) and proposes to treat all living beings as able to produce forms of thoughts, representations and interpretations. Linguistics, as the study of human language, could simply have nothing to do with this matter. However, we argue that the observation of interspecific interactions is a valuable locus to analyze pragmatically efficient actions, that unfold emergently and regardless of a “code.” Animals’ actions make sense for humans, as well as humans’ action make sense for animals, and sometimes very complex joint actions rest on this rudimentary semiosis.